Currently, Sam's coach is twice as old as Sam. When Sam started soccer 10 years ago, his coach was 3 times his age. How old is Sam now?

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions.

- anonymous

- chestercat

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this

and **thousands** of other questions

- goformit100

- anonymous

help

- anonymous

|dw:1350960568419:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

50

- anonymous

multiply 5 to both sides

- anonymous

|dw:1350960670105:dw|

- anonymous

c = 2s
c-10 = 3(s-10) --> c - 10 = 3s - 30 --> c = 3s - 20
2s = 3s - 20
s = 20
c = 40
Wow that should not have been that hard for me. Sorry it took so long

- anonymous

|dw:1350960915774:dw|

- anonymous

Now he is twice sam's age. That is where the first equation came from.
10 years ago, so start with c - 10 and s - 10, the coach was 3 times sam's age. That is where the 3 comes from. I simplified then substituted in the 2s for c to solve for s. Then I knew c

- anonymous

can you please solve the new problem on top

- anonymous

y/-2 + 5 = 12
y/-2 + 5 - 5 = 12 - 5
y/-2 = 7
-2 * y/-2 = 7 * -2
y = -14

- anonymous

\[x=\frac{ x-6 }{ 2 } =3\]\[2x=2\times \frac{ x-6 }{ 2 } =3 \times 2\]\[2x=x-6 =6\]Impossible, was there a typo in your original equation

- anonymous

|dw:1350961540644:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.